Vacancy manipulating of molybdenum carbide MXenes to enhance Faraday reaction for high performance lithium-ion batteries - Guo, Xin; Wang, Changda; Wang, Wenjie; Zhou, Quan; Xu, Wenjie; Zhang, Pengjun; Wei, Shiqiang; Cao, Yuyang; Zhu, Kefu; Liu, Zhanfeng; Yang, Xiya; Wang, Yixiu; et al. (Nano Research Energy, 2022)
"Intrinsic" strategies for manipulating the local electronic structure and coordination environment of defect-regulated materials can optimize electrochemical storage performance. Nevertheless, the structure–activity relationship between defects and charge storage is ambiguous, which may be revealed by constructing highly ordered vacancy structures. Herein, we demonstrate molybdenum carbide MXene nanosheets with customized in-plane chemical ordered vacancies (Mo1.33CTx), by utilizing selective etching strategies. Synchrotron-based X-ray characterizations reveal that Mo atoms in Mo1.33CTx show increased average valence of +4.44 compared with the control Mo2CTx. Benefited from the introduced atomic active sites and high valence of Mo, Mo1.33CTx achieves an outstanding capacity of 603 mAh·g−1 at 0.2 A·g−1, superior to most original MXenes. Li+ storage kinetics analysis and density functional theory (DFT) simulations show that this optimized performance ensues from the more charge compensation during charge–discharge process, which enhances Faraday reaction compared with pure Mo2CTx. This vacancy manipulation provides an efficient way to realize MXene's potential as promising electrodes.